No monkeys, no chocolate - Stewart, Melissa (Charlesbridge, 2013)
When you think of chocolate, you might think of a candy bar, a birthday cake, or a glass of chocolate milk. But where does chocolate come from? This book tells about the cocoa bean, which grows in the tropical rain forests and how the animals and other living things play an important part, even the monkeys.